Implementasi Media Kartu Huruf dalam Meningkatkan Kemampuan Penguasaan Kosakata Anak Usia Dini - Mercoria Soraya; Rahmadani, Ni Kadek Aris (Universitas Pendidikan Ganesha, 2023)
Learning in early childhood receives attention so that children's abilities do not progress, one of which is language learning. This research analyzes teachers' strategies for improving vocabulary mastery through letter cards. This qualitative research uses research subjects, namely 3 teachers and children aged 4-5 years, with 25 children. The data collection methods used in this research were observation techniques and interviews with teachers as primary data sources. The analysis technique used in this research is a qualitative descriptive analysis technique referring to the opinions of Miles and Huberman, with three activities: qualitative data analysis, data reduction, data presentation, and conclusion. The results of the research show that the use of letter card media is known to have several contributions to the learning process, one of which is that the use of letter cards can be a medium for letter recognition. Letter cards are also effective for helping children recognize, remember, and understand alphabet letters. Implementing letter card media in early childhood education significantly impacts language development. It can improve vocabulary mastery and practice reading and writing skills by observing the letter cards and children trying to imitate them. The research concludes that letter card media can improve vocabulary mastery abilities in young children.